Chimeric Antigen Receptor T Cells Targeting Cell Surface GRP78 to Eradicate Acute Myeloid Leukemia - Yu, Wei; Zhang, Hang; Yuan, Yuncang; Tang, Jie; Chen, Xinchuan; Liu, Ting; Zhao, Xudong (Frontiers in Cell and Developmental Biology, 2022)
Acute myeloid leukemia (AML) is a serious, life-threatening hematological malignancy. The treatment outcome of relapsed or refractory AML patients remains dismal and new treatment options are needed. Chimeric antigen receptor T cells (CART) have been successful in improving prognosis for B-lineage acute lymphoblastic leukemia and lymphoma by targeting CD19. However, CAR-T therapy for AML is still elusive, owing to the lack of tumor-specific cell surface antigen and spare hematopoietic stem cells (HSCs) in the meanwhile. Here, we generated a novel CAR construction that targets the cell surface protein GRP78 (csGRP78). We confirmed the GRP78-CAR T cells demonstrate an anti-tumor effect against human AML cells in vitro. In xenograft models, GRP78 CAR T cells effectively eliminate AML cells and protect mice against systemic leukemia, in the meanwhile, prolonging survival. In addition, GRP78-CAR T cells also specifically eradicate the primary AML patient-derived blast. Importantly, GRP78-CAR T cells spare normal HSCs, highlighting GRP78-CAR is a promising approach for the therapy of AML.